Epoxy ink and preparation method thereof

By developing a low viscosity and low dielectric constant epoxy ink, using hyperbranched epoxy resin and modified epoxy monomer, combined with biphenyl structure and silicone segments, the problems of aging of organic luminescent materials and high viscosity of packaging materials in OLED display devices are solved, and the stability and life of the device are improved.

CN119859438APending Publication Date: 2025-04-22WANHUA CHEM GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510005688.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The organic luminescent materials in OLED display devices will appear after contacting water and oxygen, resulting in device aging and reduced life. The existing packaging materials with low dielectric constants have high viscosity, making it difficult to meet the requirements of inkjet printing applications.

Method used

A low viscosity, low dielectric constant epoxy ink was developed, and epoxy ink with excellent moisture and heat aging resistance and low dielectric constant was prepared by using hyperbranched epoxy resin and modified epoxy monomer, combined with biphenyl structure and silicone segments.

Benefits of technology

It achieves the improvement of the stability and life of the device while maintaining low dielectric constant and low viscosity, and solves the problems of high water barrier packaging and aging of OLED display devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005226796060000021
    Figure BDA0005226796060000021
  • Figure BDA0005226796060000022
    Figure BDA0005226796060000022
  • Figure BDA0005226796060000031
    Figure BDA0005226796060000031
Patent Text Reader

Abstract

The invention provides epoxy ink and a preparation method thereof, the epoxy ink comprises epoxy resin, branched epoxy resin, modified epoxy resin, a cationic initiator and an auxiliary agent, and the modified epoxy resin is an oligomer obtained by addition of polydimethylsiloxane diglycidyl ether and biphenol. According to the epoxy ink, a siloxane long chain is matched with a biphenyl structure, the structure is endowed with low polarity, meanwhile, the rigidity requirement of a system is further met, hyperbranched epoxy is introduced in a combined mode, the network crosslinking density is further reduced, the polarizability of the system is reduced, and the low dielectric property of the epoxy ink is effectively improved while the mechanical property is not lost; the matching of rigid and flexible structures also supports the damp-heat aging stability of the epoxy ink, and the service life of a device can be effectively prolonged when the epoxy ink is applied to display device packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of OLED display, and in particular relates to a low-viscosity, low-dielectric-constant epoxy ink and a preparation method thereof. Background Art

[0002] OLED (Organic Light-Emitting Diode), also known as organic electroluminescence, is different from LCD display technology with backlight source. The organic light-emitting materials in OLED display technology have the characteristics of self-luminescence. The combination of RGB three-color organic light-emitting materials can be controlled by the current and voltage changes of TFT shifts to present different colors. In addition, compared with traditional liquid crystal materials, its organic light-emitting materials are low-cost and adjustable in structure, which can meet the needs of full color and flexibility. Compared with the box-forming process and backlight module assembly of traditional liquid crystal, OLED display devices are simpler to make. Therefore, OLED display technology is more in line with the development trend of the future display industry than LCD display technology, and can further meet the application needs of consumers. It has been vigorously developed in recent years. However, there are still some urgent problems to be solved in the application of OLED display technology. The most important one is that the organic light-emitting materials in OLED display devices will appear black spots after contacting water and oxygen, which will cause device aging and seriously affect the life and stability of OLED displays. Therefore, the high water-resistance packaging problem of OLED display devices is one of the key factors affecting the development of OLED display devices at this stage.

[0003] OLED devices also include other functional devices such as touch conductive layers, and the various electrical signals emitted by them also have an adverse effect on the OLED light-emitting layer. In addition, various external static electricity and electromagnetic waves may also cause OLED display devices to malfunction or reduce their lifespan. The use of packaging materials with lower dielectric constants can effectively improve electrical insulation and ensure the normal operation of display devices.

[0004] However, the dielectric constants of some existing encapsulation compositions are above 3.0, which is difficult to meet the requirements of semiconductor devices for low dielectric properties, and the disclosed low dielectric constant encapsulation compositions still have various problems. For example, patent CN114057975A discloses a bio-based polyurethane-modified acrylate, which can effectively reduce the dielectric constant and has excellent aging properties when used to prepare photocurable materials. However, the viscosity is actually too high to meet the actual inkjet printing application requirements.

[0005] Therefore, it is expected to develop a low-viscosity, low-dielectric constant epoxy ink that has a certain adhesion and excellent performance in printing, optics and wet-heat aging and can meet the requirements of low dielectric properties. Photocurable materials to solve the above technical problems. Summary of the invention

[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide an epoxy ink, a preparation method thereof and an application thereof. The epoxy ink has low viscosity and low dielectric constant, so that when it is used for sealing and bonding display devices, it can effectively extend the life and stability of the device.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides an epoxy ink, wherein the epoxy ink comprises the following components in parts by weight:

[0009]

[0010] As a preferred solution, the epoxy ink comprises the following components in parts by weight:

[0011]

[0012]

[0013] The viscosity of the epoxy ink provided by the present invention is not higher than 100 cps, the wet heat aging property is under the conditions of 85°C and 85% RH, the reliability is greater than 504h, and the dielectric constant is less than 2.6 under the conditions of film thickness of 100 μm and 100 Hz.

[0014] The branched epoxy resin is preferably a hyperbranched epoxy resin.

[0015] The modified epoxy monomer is prepared by the addition reaction of polydimethylsiloxane diglycidyl ether and biphenol.

[0016] Preferably, the structural formula of the polydimethylsiloxane diglycidyl ether is as follows:

[0017]

[0018] The number of repeating units n is 0 to 20, preferably 1 to 10.

[0019] Preferably, the molar ratio of polydimethylsiloxane diglycidyl ether to biphenol is (1.5-2.5):1.

[0020] Preferably, the molar ratio of the epoxy group in the polydimethylsiloxane diglycidyl ether to the phenolic hydroxyl group in the biphenol is 2:1.

[0021] Preferably, the polydimethylsiloxane diglycidyl ether reacts with diphenol under alkaline catalyst conditions.

[0022] Preferably, the alkaline catalyst may be an alkali metal hydroxide, an alkali metal carbonate, etc., and the type of the alkaline catalyst is not particularly limited. Potassium hydroxide, sodium hydroxide, etc. are preferred.

[0023] Preferably, the polydimethylsiloxane diglycidyl ether reacts with diphenol at 60-90°C.

[0024] Preferably, during the preparation of the modified epoxy monomer, biphenol is added to the polydimethylsiloxane diglycidyl ether in multiple portions or slowly to ensure that the biphenol reacts fully.

[0025] Preferably, diphenol is added in three or more times, preferably in ten or more times.

[0026] Preferably, the number average molecular weight of the modified epoxy monomer is no more than 1500.

[0027] Preferably, the epoxy resin includes any one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, glycidylamine epoxy resin, resorcinol epoxy resin, biphenyl epoxy resin, sulfide epoxy resin, diphenyl ether epoxy resin, dicyclopentadiene epoxy resin, naphthalene epoxy resin, alkyl polyol epoxy resin, and rubber modified epoxy resin.

[0028] Preferably, the epoxy diluent is one or more selected from ethylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, phenyl glycidyl ether, benzyl glycidyl ether, polypropylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether and oxetane-type epoxy diluents.

[0029] Preferably, the cationic initiator includes ionic aromatic diazonium salts, diaryl iodonium salts, triaryl sulfonium salts, alkyl sulfonium salts, iron aromatic salts, etc., and non-ionic photoacid-generating photocationic polymerization initiators, for example, nitrobenzyl esters, sulfonic acid derivatives, phosphates, phenol sulfonates, diazonaphthoquinones, N-hydroxyimide sulfonates, etc.

[0030] Preferably, the epoxy ink comprises 0.3 to 7 parts by weight of an auxiliary agent.

[0031] Preferably, the auxiliary agent includes one or more of a defoamer, an inhibitor, a coupling agent or a leveling agent.

[0032] The present invention also provides a method for preparing the epoxy ink, comprising the following steps: mixing epoxy resin, branched epoxy resin, modified epoxy monomer, epoxy diluent, cationic initiator and auxiliary agent to obtain the epoxy ink.

[0033] Preferably, in the method for preparing the epoxy ink, the mixing time is not less than 2 hours.

[0034] Preferably, in the method for preparing the epoxy ink, the mixing is performed under stirring, and the stirring speed is not less than 1500 rpm.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] The low dielectric constant epoxy ink provided by the present invention adopts a hyperbranched epoxy resin, which can effectively increase the hole ratio in the cross-linked system and reduce the overall polarization density. The modified epoxy monomer is a rigid matrix grafted with a flexible chain segment. The biphenyl structure gives the system a rigid network to ensure the resistance to wet heat aging. The combination with the branched epoxy resin may further increase the free volume of the cross-linked network and reduce the polarization density of the system. At the same time, the introduction of a toughened siloxane chain segment further ensures the adhesion of the system and the stress release during the aging process. The low-polarity siloxane chain segment can further reduce the overall polarity in the cross-linked network with low polarization density, achieving low dielectric performance. Solve the touch drift problem of touch screen OLED devices and improve the touch sensitivity of the device. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0038] (1) The raw material information involved in the specific implementation of the present invention is as follows:

[0039] Bisphenol A epoxy resin (EXA-850CRP): DIC resin, industrial product;

[0040] Cycloaliphatic epoxy resin (8010): Daicel resin, industrial product;

[0041] 1,4-Butanediol diglycidyl ether: Anhui Xinyuan, industrial products;

[0042] Hyperbranched epoxy resin (HyPer E102): Wuhan hyperbranched resin, industrial product;

[0043] Polydimethylsiloxane diglycidyl ether: McLean, industrial product;

[0044] Bisphenol A: Aowei Chemical, industrial products;

[0045] 3,3'-(oxybismethylene)-bis-(3-ethyl)-oxetane (S221): Donghua New Materials, industrial products;

[0046] 3-Glycidyloxypropyltrimethoxysilane: Shin-Etsu, industrial product;

[0047] Diphenyl-(4-phenylthio)phenylsulfonium hexafluoroantimonate: San-Apro, reagent grade.

[0048] Preparation Example 1

[0049] Modified epoxy monomer 1: 436 g of polydimethylsiloxane diglycidyl ether (n=1) was added to a reaction flask equipped with a stirring device, a temperature control device, and a condensing device, and the temperature in the flask was ensured to be 60° C. and the speed was 200 rpm. 0.5 g of biphenyl diphenol was added to the reaction flask each time. After the biphenyl diphenol added last time was dissolved, the next addition was performed. A total of 46.55 g of biphenyl diphenol was added. After the addition was completed, the speed was maintained at 200 rpm and 60° C. for 20 minutes. The phenolic hydroxyl group content was analyzed by an infrared spectrometer. After the phenolic hydroxyl peak disappeared, a polydimethylsiloxane type glycidyl ether containing a biphenyl structure was obtained;

[0050] Preparation Example 2

[0051] Modified epoxy monomer 2: 362 g of polydimethylsiloxane diglycidyl ether (n=0) was added to a reaction flask equipped with a stirring device, a temperature control device, and a condensing device, and the temperature in the flask was ensured to be 60°C and the speed was 200 rpm. 0.5 g of biphenyl diphenol was added to the reaction flask each time. After the biphenyl diphenol added last time was dissolved, the next addition was performed. A total of 46.55 g of biphenyl diphenol was added. After the addition was completed, the speed was maintained at 200 rpm and 60°C for 20 minutes. The phenolic hydroxyl group content was analyzed by an infrared spectrometer. After the phenolic hydroxyl peak disappeared, a polydimethylsiloxane type glycidyl ether containing a biphenyl structure was obtained;

[0052] Preparation Example 3

[0053] Modified epoxy monomer 3: 732 g of polydimethylsiloxane diglycidyl ether (n=5) was added to a reaction flask equipped with a stirring device, a temperature control device, and a condensing device, and the temperature in the flask was ensured to be 80°C and the speed was 200 rpm. 0.5 g of biphenyl diphenol was added to the reaction flask each time. After the biphenyl diphenol added last time was dissolved, the next addition was performed. A total of 46.55 g of biphenyl diphenol was added. After the addition was completed, the speed was maintained at 200 rpm and 60°C for 30 minutes. The phenolic hydroxyl group content was analyzed by an infrared spectrometer. After the phenolic hydroxyl peak disappeared, a polydimethylsiloxane type glycidyl ether containing a biphenyl structure was obtained;

[0054] Examples 1 to 5 and Comparative Examples 1 to 3

[0055] Add the modified epoxy monomer and epoxy diluent into a double planetary stirring kettle, control the temperature to 25°C, and the vacuum condition to a gauge pressure of -0.1MPa. After stirring at a speed of 2000rpm for 40min, add epoxy resin, branched epoxy resin, and cationic initiator in sequence and stir at a speed of 2000rpm for 40min. Finally, add the optional auxiliary agent and stir at a speed of 1000rpm for 30min, stir at a speed of 1500rpm for 30min, stir at a speed of 2000rpm for 40min, and finally release the pressure and take out to obtain epoxy ink.

[0056] The raw material selection and dosage of each component in the above Examples 1 to 5 and Comparative Examples 1 to 3 are shown in Table 1, where the unit of dosage is "g".

[0057] Table 1 Examples and Comparative Examples Raw Materials and Dosages

[0058]

[0059] Performance Test:

[0060] 1. Viscosity

[0061] Take an appropriate amount of light-curing adhesive sample and add it to the viscometer (LV-SSR rotary viscometer), and test the viscosity of the sample at 25°C.

[0062] 2. Surface tension

[0063] 30 mL of photocuring adhesive sample was placed in a beaker, and the surface tension of the sample was tested using a bubble method surface tension meter (SITA pro line T15).

[0064] 3. Refractive index

[0065] The refractive index of liquid ink in the visible light range is characterized by using Abbe refractometer.

[0066] 4. Light transmittance

[0067] The photocurable adhesive was printed on the electronic glass substrate using an inkjet printer, and a UV-LED lamp with a wavelength of 395 nm was used to apply 1500 mJ / cm 2 The photocurable adhesive was cured into a 12 μm thick film with energy, and the light transmittance of the film was tested by a colorimeter (HunterLab UltraScan VIS).

[0068] 5. Curing rate

[0069] The curing rate of the photocuring adhesive sample was tested using an FT-IR device (Thermo Fisher Nicolet iS5). The specific process was as follows: 1 mL of the photocuring adhesive sample was added between two release films, and then pressure was applied to spread the photocuring adhesive evenly on the release films. A UV-LED lamp with a wavelength of 395 nm was used to apply 1500 mJ / cm 2 The energy of the light-curing adhesive is cured into a film of 20-30 microns thick. The samples were tested before and after curing at 1635 cm -1 (C=C) and 1720cm -1 The intensity of the absorption peak near (C=O) was used to calculate the curing rate using the following formula:

[0070] Curing rate (%) = |1-(A / B)| × 100%

[0071] Where A represents the solidified film at 1635cm -1 and 1720cm -1 The intensity ratio of the absorption peaks near 1635cm -1 and 1720cm -1 The intensity ratio of nearby absorption peaks.

[0072] 6. Double 85 aging

[0073] The photocurable adhesive was printed on the electronic glass substrate using an inkjet printer, and a UV-LED lamp with a wavelength of 395 nm was used to apply 1500 mJ / cm 2 The photocurable adhesive was cured into a 12μm thick film with 100% energy. The film was aged in a constant temperature and humidity chamber at 85°C and 85% humidity for 504 hours to observe whether the film surface was cracked or wrinkled. The film surface that was well preserved was recorded as ○, and the film surface that was abnormal was recorded as ×.

[0074] 7. Dielectric constant

[0075] The photocurable adhesive sample was printed on an ITO glass substrate using an inkjet printer, and a UV-LED lamp with a wavelength of 395 nm was used to apply 1500 mJ / cm 2 The photocurable adhesive sample was cured into a 12μm thick film using energy. Silver electrodes were prepared on the film using vacuum evaporation equipment to form a three-layer structure of ITO / film / silver. The capacitance of the cured film was tested using an impedance analyzer (Keysight Technologies, 4990A), and the dielectric constant was calculated using the following formula:

[0076]

[0077] Among them, C p is the equivalent parallel capacitance of the test film (F);

[0078] t m is the average thickness of the tested film (m);

[0079] A is the surface area of ​​the electrode (m 2 );

[0080] d is the diameter of the electrode (m);

[0081] ε0 is the dielectric constant of free space = 8.854×10 -12 (F / m).

[0082] 8. Inkjet performance

[0083] The inkjet printing performance of the photocurable adhesive sample was tested by a piezoelectric drop-on-demand print head (KM1024i Konica Minolta). The inkjet head temperature was 25-35°C and the speed was 3μm / sec. Spherical droplets were formed during inkjet printing without ink flying. The results with good wettability were recorded as ○, and the results with abnormal inkjet printing were recorded as ×.

[0084] Table 2 Test results of embodiments and comparative examples

[0085]

[0086] It can be seen from the data in Table 2 that the epoxy ink provided by the present invention has excellent printing performance, optical performance, resistance to moisture and heat aging and dielectric properties. After aging, the product shows no film surface abnormality, which solves the overall requirements of OLED devices for packaging ink aging, dielectric properties and aging, effectively improves device stability and extends device service life.

[0087] The applicant declares that the present invention illustrates a highly water-resistant epoxy ink and its preparation method and application through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. An epoxy ink, characterized in that: The epoxy ink comprises the following components in parts by weight:

2. The epoxy ink according to claim 1, characterized in that: The epoxy ink comprises the following components in parts by weight:

3. The epoxy ink according to claim 1 or 2, characterized in that: The branched epoxy resin is preferably a hyperbranched epoxy resin.

4. The epoxy ink according to any one of claims 1 to 3, characterized in that: The modified epoxy monomer is prepared by the addition reaction of polydimethylsiloxane diglycidyl ether and biphenyl diphenol; Preferably, the structural formula of the polydimethylsiloxane diglycidyl ether is as follows: wherein the number of repeating units n is 0 to 20, preferably 1 to 10; Preferably, the molar ratio of polydimethylsiloxane diglycidyl ether to biphenyl diphenol is (1.5-2.5):1; Preferably, the molar ratio of the epoxy group in the polydimethylsiloxane diglycidyl ether to the phenolic hydroxyl group in the biphenol is 2:1; Preferably, the polydimethylsiloxane diglycidyl ether reacts with diphenol under alkaline catalyst conditions; Preferably, the alkaline catalyst is one or more of alkali metal hydroxides and alkali metal carbonates; Preferably, the polydimethylsiloxane diglycidyl ether reacts with diphenol at 60 to 90°C; Preferably, during the preparation of the modified epoxy monomer, the biphenol is added to the polydimethylsiloxane diglycidyl ether in multiple portions or slowly to ensure that the biphenol is fully reacted; Preferably, biphenol is added in three or more times, preferably in ten or more times; Preferably, the number average molecular weight of the modified epoxy monomer is no more than 1500.

5. The epoxy ink according to any one of claims 1 to 4, characterized in that: The epoxy resin includes any one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, glycidylamine epoxy resin, resorcinol epoxy resin, biphenyl epoxy resin, thioether epoxy resin, diphenyl ether epoxy resin, dicyclopentadiene epoxy resin, naphthalene epoxy resin, alkyl polyol epoxy resin, and rubber modified epoxy resin; Preferably, the epoxy diluent is one or more selected from ethylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, phenyl glycidyl ether, benzyl glycidyl ether, polypropylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether and oxetane type; Preferably, the cationic initiator includes one or more of ionic aromatic diazonium salts, diaryl iodonium salts, triaryl sulfonium salts, alkyl sulfonium salts, and iron aromatic salts, and / or one or more of non-ionic photoacid-generating photocationic polymerization initiators such as nitrobenzyl esters, sulfonic acid derivatives, phosphates, phenol sulfonates, diazonaphthoquinones, and N-hydroxyimide sulfonates.

6. The epoxy ink according to any one of claims 1 to 5, characterized in that: The epoxy ink includes 0.3 to 7 parts by weight of an auxiliary agent; Preferably, the auxiliary agent includes one or more of a defoamer, an inhibitor, a coupling agent or a leveling agent.

7. The method for preparing epoxy ink according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: mixing epoxy resin, branched epoxy resin, modified epoxy monomer, epoxy diluent, cationic initiator and auxiliary agent to obtain the epoxy ink.

8. The preparation method according to claim 7, characterized in that: The mixing time is not less than 2 hours; and / or, The mixing is carried out under stirring conditions, and the stirring speed is not less than 1500 rpm.